Personal hygiene and taking into account the preventive measures and safety among healthcare providers - Ali, Ghona Abd El-Nasser; Mohamed, Nadia; Y. Mahdy, Abeer (International Journal of Advanced Nursing Studies, 2018)
Negligence of personal hygiene and safety practices among healthcare personnel is not only a major risk factor in the spread of infection, but is in many instances an abuse of human rights.Aim: the study aim was to assess the personal hygiene and taking into account the preventive measures and safety among healthcare providers.Tools: An interview questionnaire sheet and personal hygiene and vaccination status.Subject and methods: A descriptive design was used in the current study and all available doctors, nurses and housekeeper in the days of data collection.Results: It was found that the majority of physicians (76.2%) were holders of a bachelor degree of medicine, while the majority of nurses were holders of a diploma /technical of nursing and the majority of housekeepers were holders of a basic education. There were highly statistical significant differences based on study groups, profession, and qualifications.Conclusion: The adherence of the majority of healthcare provider with personal hygiene and safety measures were ranged from poor to fair. There was a relationship between availability of protective equipments barrier and personal hygiene practices and safety measures. Recommendations: A significant efforts are needed to enhance universal precaution compliance among caregivers includes training, strict supervision with disciplinary measures for poor compliance with improve the facilities available and equipments for personal hygiene and safety.